2020
DOI: 10.1109/access.2020.3045152
|View full text |Cite
|
Sign up to set email alerts
|

Pricing and Coordination of Green Closed-Loop Supply Chain With Fairness Concerns

Abstract: Due to serious environmental pollution and waste of resources, the government advocates the development of a sustainable circular economy, and academia and manufacturing are gradually paying attention to the green closed-loop supply chain. In this paper, a green closed-loop supply chain consisting of a manufacturer and a retailer is considered. The manufacturer would cost a great deal to recycle waste products for remanufacturing while developing and producing green products, which may concern about the fairne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Yu et al [9] investigated ordering strategies in a dual-channel supply chain context with three scenarios: manufacturer with fairness concerns, retailer with fairness concerns, and bidirectional fairness concerns, for a dual-channel supply chain context, and used an inventory parceling strategy to achieve dual-channel supply chain coordination. Zhang and Li [10]discussed the impact of manufacturer fairness concerns and whether retailers consider manufacturer fairness concerns on supply chain greenness in a green closed-loop supply chain, and supply chain coordination was achieved using revenue sharing contracts. In addition, other scholars focused on operational strategies with fairness concerns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yu et al [9] investigated ordering strategies in a dual-channel supply chain context with three scenarios: manufacturer with fairness concerns, retailer with fairness concerns, and bidirectional fairness concerns, for a dual-channel supply chain context, and used an inventory parceling strategy to achieve dual-channel supply chain coordination. Zhang and Li [10]discussed the impact of manufacturer fairness concerns and whether retailers consider manufacturer fairness concerns on supply chain greenness in a green closed-loop supply chain, and supply chain coordination was achieved using revenue sharing contracts. In addition, other scholars focused on operational strategies with fairness concerns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al [ 4 ] studied the effect of government subsidies on members’ revenues in GSCM, and the results showed that they have a positive influence on the selling channel selection. Zhang and Li [ 5 ] discussed the optimal results for a point firm in GSCM and pointed out that the greenness level has a vast impact on the GSCM. Dey et al [ 6 ] and Yan et al [ 7 ] discussed the effects of different pricing contracts on greenness level decisions in two-period GSCM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the majority of works (Li et al, 2019b;Zhang and Li, 2020;Fan et al, 2022), we model the demand function as a linear function of retail price 𝑝 𝑖 (𝑖 = 1, 2) and the service level 𝑠 𝑖 .…”
Section: Model Settingmentioning
confidence: 99%